Airborne Mapping Reveals Emergent Power Law of Arctic Methane Emissions - Clayton D. Elder; David R. Thompson; Andrew K. Thorpe; Philip Hanke; Katey M. Walter Anthony; Charles E. Miller (Geophysical Research Letters)
Abstract Methane (CH4) emissions from thawing permafrost amplify a climate warming feedback. However, upscaling of site‐level CH4 observations across diverse Arctic landscapes remains highly uncertain, compromising accuracy of current pan‐Arctic CH4 budgets and confidence in model forecasts. We report a 30,000‐km2 survey at 25‐m2 resolution (~1 billion observations) of CH4 hotspot patterns across Alaska and northwestern Canada using airborne imaging spectroscopy. Hotspots covered 0.2% of the surveyed area, concentrated in the wetland‐upland ecotone, and followed a two‐component power law as a function of distance from standing water. Hotspots decreased sharply over the first 40 m from standing water (y = 0.21×−0.649, R2 = 0.97), mirroring in situ flux observations. Beyond 40 m, CH4 hotspots diminished gradually over hundreds of meters (y = 0.004×−0.164, R2 = 0.99). This emergent property quantifies the distribution of strong methanogenic zones from site to regional scales, vastly improving metrics for scaling ground‐based CH4 inventories and validation of land models.